ANALISIS LAYANAN BIMBINGAN KELOMPOK TENTANG PERKEMBANGAN EMOSI REMAJA KELAS X SMA SANTUN UNTAN PONTIANAK - Marselina, Selly (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractGroup guidance services is a guidance process conducted in groups by teachers of counseling and counseling in schools to prevent the occurrence of problems in learners. Learners who are given services in order to avoid problems that may arise due to excessive emotions so that learners are able to manage, control and control emotions well. The method used is descriptive method and the research form is survey study. The population in this study as many as 30 students class X SMA SANTUN UNTAN Pontianak. This research uses quantitative approach. Data collection techniques used are indirect communication techniques with data collection tools in the form of questionnaires, indirect communication with data collection tools interviews, and documentary techniques with data collection tools in the form of documentation. While the technique of data analysis using the formula percentage. Based on the results of data analysis from this study the group guidance services about the development of teen emotions reached the score in the category of "Very Good" with percentage 93.88%. This suggests that group guidance services on adolescent emotional development have been well implemented by learners and group counseling activities are well implemented.Â Keyboard : Group Guidance Services, Emotional, Youth DevelopmenÂ